Remoção parcial de tecido cariado em lesões de cárie profundas de dentes permanentes - Jardim, Juliana Jobim (2010)
The partial removal of carious dentine was studied by means of a literature review and a multicenter randomized controlled clinical trial. The clinical trial compared the effectiveness of an alternative treatment for deep caries lesions and the stepwise excavation in Public Health Services in Brazil. The treatment consists of partial removal of carious dentine followed by restoration in one session. A cost-effectiveness analysis the two treatments was performed. The clinical performance of amalgam and resin restorations placed in deep caries lesions with or without decayed tissue beneath them was also evaluated. Inclusion criteria: patients with ≥ nine years old, permanent molars with deep caries lesions and absence of periapical alterations, pulp sensitivity; absence of spontaneous pain; negative percussion test. The subjects were assigned to: test-group - partial removal of carious dentine (PDR) and restoration, and control-group - stepwise excavation (SW). SW consists of partial removal of carious tissue, indirect pulp capping with calcium hydroxide cement; temporary filling; cavity re-opening after 60 days, removal of the remaining soft carious tissue and filling. Clinical and radiological exams were performed annually. The outcomes were: (1) pulp sensitivity to cold test and absence of periapical alterations, assuming those parameters as indicators of pulp vitality; and (2) success of the restoration. To determine the cost-effectiveness of the treatments, the discounted cash flow method was adopted. The data were submitted to Kaplan-Meier, Log-rank test and logistic regression analysis, P<0.05. There were performed 299 treatments, 146 SW and 153 tests. There were no differences between the groups regarding baseline characteristics - age, gender and family income. The number of teeth evaluated after one and two years were 180 and 122. After one year of treatment performance, the therapy success rates were 97.9% and 74.1% of success in test and control groups respectively (P<0.000). After 2 years of follow-up, therapy survival rates of PDR and SW were 93.7% and 73.3% respectively (P=0.000). A total of 29 therapeutic failures were observed: PDR group - pulpitis (n=3), osteitis (n=1), hyperemia (n=2); SW group - pulpitis (n=15), necrosis (n=6), extraction (n=1) and restoration fracture (n=1). None of the variables studied showed a significant causal influence on the success rate, besides the type of treatment. After two year of follow-up, 181 restorations had been evaluated, 86 from the SW group and 95 from the PDR group; 65.8% were from the resin composite group and 34.2% were amalgam restorations. The survival analysis of the treatment associated with the filling material showed no difference in the rate of success (P=0.564). Regarding the treatment, both groups presented a similar rate of success: SW=95.3% and PDR=94.7% (P=0.928). Resin composite restorations presented 96.8% of success and amalgam restorations presented 94.1% of success (P=0.446). The reason for failure was fracture of filling material. The PDR provides an economy of R$ 143.37 (67.78%) per treatment compare to SW and 2.39% in the overall economy in the annual cost of the public health center. Partial caries removal could be performed as definitive treatment and the procedure of re-opening the cavity to remove the residual infected dentine is not necessary. The maintenance of carious dentine does not interfere in the maintenance of pulp vitality. The presence of decayed tissue in deep caries lesions does not seem to interfere with the survival of the restorations. Performing the partial removal of carious dentine in one session generates benefits for the public finances (direct economy), for the public health services (increase in number of treatments performed) and for the patients (comfort and time).